Beyond the looking glass : narcissism and female stardom in studio-era Hollywood - Salzberg, Ana (Berghahn Books, 2014)
As living subjects rather than static icons, studio-era Hollywood actresses actively negotiated a balance between their public personas, film roles, and corporeal presence. The contemporary audience's engagement with the experience of these actresses unsettles the traditional model of narcissistic identification, which divides the off-screen spectator from his/her on-screen ideal. Exploring the fan's desire for a material connection to the performer -- as well as the star's own dialogue between embodied experience and idealized image -- Beyond the Looking Glass traces on- and off-screen representations of narcissistic femininity in classical Hollywood through studies of stars like Greta Garbo, Ava Gardner, and Marilyn Monroe. Merging historical and theoretical concerns, with particular attention to the resonance of golden-age Hollywood in new media, this book explores the movie screen as a medium of shared experience between spectator and star. --Provided by publisher.